NQO1 promotes an aggressive phenotype in hepatocellular carcinoma via amplifying ERK‐NRF2 signaling. Issue 2 (13th December 2020) - Yang, Yun; Zheng, Jie; Wang, Mengchao; Zhang, Jin; Tian, Tao; Wang, Zhiheng; Yuan, Shengxian; Liu, Lei; Zhu, Peng; Gu, Fangming; Fu, Siyuan; Shan, Yunfeng; et al.
Abstract: Patients with hepatocellular carcinoma (HCC) are usually diagnosed at the later stages and have poor survival outcomes. New molecules are urgently needed for the prognostic predication and individual treatment. Our study showed that high levels of NQO1 expression frequently exist in HCC with an obvious cancer‐specific pattern. Patients with NQO1‐high tumors are significantly associated with poor survival outcomes and serve as independent predictors. Functional experiments showed that NQO1 promotes the growth and aggressiveness of HCC in both in vitro and in vivo models, and the underlying mechanism involved NQO1‐derived amplification of ERK/p38‐NRF2 signaling. Combined block of ERK and NRF2 signaling generated stronger growth inhibition compared with any single block, especially for HCC with high‐NQO1. Therefore, NQO1 is a potential biomarker for HCC early diagnosis and prognosis prediction, and also attractive for cancer‐specific targets for HCC treatment. Abstract : Patients with NQO1‐high tumors are significantly associated with poor survival outcomes. NQO1 promotes the growth and aggressiveness of HCC in both in vitro and in vivo models; the underlying mechanism involves NQO1‐derived amplification of ERK/p38‐NRF2 signaling. NQO1 is a potential biomarker for HCC early diagnosis and prognosis prediction, and also attractive for cancer‐specific targets for HCC treatment.